The first Population Estimate of some Herbivores in Garumara National Park, West Bengal - Singhal, Niraj; Mukhopadhyay, Arun (Indian Forester, 1998)
The first population estimation of six main herbivorous species, viz. Gaur, Wild Boar, Barking Deer, Spotted Deer, Hog Deer and Sambar was carried out in Garumara National Park, West Bengal after dividing the P.A. into three major ecological habitat zones - grassland, plantation and natural forest. Direct sighting of animals was recorded and density of the population was determined. An area of 27.7 km2 was surveyed out of total area of 79.44 km2. The study indicates good density of Gaur and Wild Boar in the P.A. and relatively low density of Sambar and Spotted Deer.